Malignant Phyllodes Tumor: Imaging Features With Histopathologic Correlation. Issue 6 (25th August 2021) - Lee, Jane S; Chang, Jodie; Hagemann, Ian S; Bennett, Debbie L
Abstract: Phyllodes tumors (PT) are rare fibroepithelial lesions of the breast that commonly present as rapidly enlarging, palpable masses. Phyllodes tumors may be classified as benign, borderline, or malignant on the basis of histopathologic analysis. Although malignant PT cannot be distinguished from benign PT on the basis of imaging findings alone, studies suggest that malignant PT tend to be larger and irregular in shape, and they are less likely to have circumscribed margins. If biopsy results are indeterminate, excisional biopsy should be performed. Malignant PT can be difficult to distinguish histologically from sarcomas and spindle cell metaplastic breast carcinoma; the distinction is important for prognosis and treatment. Malignant PT are treated surgically with wide local excision, without a clear role for adjuvant radiation or chemotherapy in most cases. Nearly one-third of malignant PT recur locally, usually within a few years after initial diagnosis. Distant metastatic disease is rare, and the five-year overall survival rate of malignant PT is close to 80%. The purpose of this article is to review the clinical presentation, imaging appearance, histopathology, and management of malignant PT.